Restating the Seyed Morteza’s Sarfah Theory - Nekounam, Jafar (Journal of History Culture and Art Research, 2017)
During the third to sixth century, a theory about miraculous aspects of the Quran, named the Sarfah Theory, was proposed. Seyed Morteza was one of the eminent fans of this theory. Although he had been attracted to this theory by complying with the Mu’tazilli System, he played the most significant role in developing this theory by his independent compilation named “Almouzeh-The Explanation”. His scientific domination over literature, poetry, language, jurisprudence and rules, prevents us from neglecting his theory, and ignore his reasons and challenges about Sarfah theory. The issue that someone like Seyed Morteza claims that the text of Quran is devoid of miracles and its miracles are outside of its text, needs to be precisely investigated. However, his exposition of Sarfah cannot be accepted, but as it seems a new exposition of this theory can be provided and generally a good advocation of Seyed Morteza’s theory can be presented. In this paper, we accompany Seyed Morteza and claim that the thaumaturgy of Quran has aspects outside of its text. But we also declare that this miracle is associated with the way of getting through Quran. This exposition of Sarfah would be that: God has denied the Quranic revelation gift for anyone but Prophet Muhammad.